2014
DOI: 10.1186/1471-2474-15-266
|View full text |Cite
|
Sign up to set email alerts
|

Association between obesity and magnetic resonance imaging defined patellar tendinopathy in community-based adults: a cross-sectional study

Abstract: BackgroundPatellar tendinopathy is a common cause of activity-related anterior knee pain. Evidence is conflicting as to whether obesity is a risk factor for this condition. The aim of this study was to determine the relationship between obesity and prevalence of magnetic resonance imaging (MRI) defined patellar tendinopathy in community-based adults.Methods297 participants aged 50–79 years with no history of knee pain or injury were recruited from an existing community-based cohort. Measures of obesity include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 41 publications
1
28
1
Order By: Relevance
“…Multiple studies focused on risk factors of PT [9, 34, 37, 41]. However, no previous study identified evidence-based prognostic outcome factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies focused on risk factors of PT [9, 34, 37, 41]. However, no previous study identified evidence-based prognostic outcome factors.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced muscular flexibility has been determined as an intrinsic risk factor for PT in athletes [2, 41]. Additionally, PT is commonly observed in older and obese patients as well as in subjects exhibiting an increased vastus medialis muscle size [9, 33, 34]. Some investigators believe that the inferior pole of the patella has a propensity to impinge upon the deep surface of the proximal patellar tendon during knee flexion [14, 21, 33].…”
Section: Introductionmentioning
confidence: 99%
“…The difference was explained by a mechanical pathogenesis of patellar tendinopathy. 67 According to a recent systematic review, good evidence supports obesity as an overall risk factor for tendinopathy. 68 Upper-extremity pain is a common complaint contributing to decreased HRQL, an important cause of occupational disability, and a substantial contributor to health care spending.…”
Section: Upper-and Lower-extremity Painmentioning
confidence: 99%
“…The presence of intramuscular fat in obese subjects could also be related to the evidence that metabolic dysregulation, through an adipose tissue-associated inflammation process, could also play a role in knee OA 12 . Recently, some interest has been devoted to the relationships between obesity, metabolic diseases and tendinopathies [13][14][15][16][17] . There is some evidence that obesity is a risk factor also for tendinopathy at different districts in community based adults, including the patellar tendon 15 .…”
Section: Introductionmentioning
confidence: 99%